Differences according to modalities, distances and genders of how the triathletes carry their bicycles for the boxes during the first transition in the Spanish Championships - Romero-Ramos, Óscar; Fernández-Rodríguez, Emilio; Merino-Marban, Rafael; Mayorga-Vega, Daniel (My University, 2019)
Introduction The purpose was to compare the proportion in the use (by elite or pro category) of the 4 types of hold-riding the bicycle during the transition between triathletes’ sex (men and women), distance or modality (Olympic, sprint, long and cross) at the Triathlon Spanish Championships. Method The sample was composed by 648 Spanish triathletes, participants of eight elite Spanish championship triathlon during 2016. Results Most of triathletes hold-ride the bike by the seat only while driving it (76.2%), followed by the handlebar (14.9%), seat-handlebar (7.1%) and stem styles (1.9%). The same tendency was showed within sex, category and race subcategories, except for Olympic (seat style was used for the 95% of triathletes), sprint (seat and handlebar styles were similar), and long (seat-handlebar and stem styles were equal). The results showed that there were statistically significantly differences in the proportion of triathletes that used each hold-riding of the bicycle between sex, race, and sex-race subcategories (p < 0.05). As regards the sex race analyses, although both, men and women, elite triathletes mostly used the seat style during the short (Olympic), sprint and long distances, while during cross race men used more the handlebar style, women used the seat style. However, when men and women were compared within each race subcategory independently, statistically significantly differences were not found (p > 0.05; Cramer´s V = 0.000-0.244). Discussion The difference between men and women is that men have twice the grip on the handlebars. The videos show that this may be because the groups of men in the boxes are greater than those of the women, and this sometimes forces them, to take the bike by the handlebar to control it better and avoid incidents. While in the Olympic, sprint and long-distance elite triathletes mostly used the seat style, and in the cross race the handlebar style.
Keywords: Triathlon; T1; Boxes